The Effect of Different Feeding Frequency on Survival and Growth of Asang Fish Larva (Osteochilus haselti C.V) - Mas Eriza; Amelia Sriwahyuni Lubis; M. Amri; Arlius Arlius; Elfrida Elfrida (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
This study aimed to analyze the effect of the frequency of commercial feeding on the survival and growth of Asang fish larvae. This research was conducted from August to October 2021 at the Integrated Laboratory of the Faculty of Fisheries and Marine Sciences, Bung Hatta University, Padang, West Sumatra. This study used an experimental method with 3 treatments and 4 replications. The treatments in this study were Treatment A = Feed frequency 2 times a day; Treatment B = Feed frequency 3 times a day; and Treatment C = Feed frequency 4 times a day. Parameters observed in this study were survival of fish larvae (%), specific growth rate (%/day), absolute weight growth (mg), absolute length growth (mm), feed utilization efficiency and water quality. The data obtained from the research results were analyzed by one way ANOVA using SPSS 26.0 software. The results showed that the frequency of commercial feeding had a significant effect on the survival and absolute length growth of Asang fish larvae (P<0.05) and had no significant effect on the absolute weight growth of Asang fish larvae (P>0.05). Treatment C was the best frequency which resulted in the highest absolute survival (35.78±2.00), growth in absolute weight of ang fish larvae (15.03±1.64 mg) and length (5.03±0.16 mm). feeding according to gastric emptying of Asang fish larvae.